Effect of Different Cobalt Concentrations on Tungsten Trioxide Photoelectrodes for Use in Solar Water Oxidation. Issue 4 (13th January 2015) - Kollender, Jan Philipp; Mardare, Andrei Ionut; Hassel, Achim Walter
Abstract : High throughput screening of photoelectrochemical activity was performed on a WO3 -CoO thin film combinatorial library using photoelectrochemical scanning droplet cell microscopy. The compositional spread was deposited using co-evaporation of WO3 and metallic Co followed by thermal oxidation in pure oxygen. The elemental compositional mapping along the library via EDX revealed a total compositional gradient of 29 at%. The microstructure and crystallographic properties were investigated via SEM and XRD. Small cubic grains of WO3 were identified on the surface for Co contents up to 13 at% while CoO remained amorphous along the entire library in mixture with both cubic and orthorhombic WO3 . A remarkable peak of photoactivity was identified in a compositional range of 7 to 15 at% Co with current density values in excess of 110 μA cm −2 for an applied potential of 1 V vs. SHE. Surface XPS investigations were used for correlating the bulk and surface composition of the library. In the compositional region corresponding to the maximum photoactivity peak, a constant W/Co atomic ratio was measured on the surface while the corresponding bulk ratio was increasing. This effect could be the result of a mixed contribution from an enhanced electrocatalytic activity for oxygen evolution on the surface and increased bulk radiation absorption.